Breaking the reproductive barrier of divergent species to explore the genomic landscape - Gilles, A.; Thevenin, Y.; Dione, F.; Martin, J.-F.; Barascud, B.; Chappaz, R.; Pech, N. (Frontiers in Genetics, 2022)
Background: Climate change will have significant consequences for species. Species range shifts induce the emergence of new hybrid zones or the spatial displacement of pre-existing. These hybrid zones may become more porous as alleles are passed from one species to another. Currently, hybridisation between highly divergent species living in sympatry seems extremely limited. Indeed, this phenomenon involves breaking two barriers. The first is the pre-mating barrier, related to the reproductive phenology of the two species. The second is the post-zygotic barrier, related to the genetic divergence between these species. Here, we were interested in identifying new hybridisation patterns, and potential implications especially in the context of environmental modifications. Methods: We sampled Telestes souffia and Parachondrostoma toxostoma wild specimens from different locations across France and genotyped them for SNP markers. We identified discriminant loci using F1-hybrid specimens and parental species, and performed principal component analysis and Bayesian model–based clustering to analyze phylogenetic information. Furthermore, we assessed deviation in allele frequency from F1 to F2 and for Hardy–Weinberg equilibrium for F2, and assessed gene function associated with two F2 cohorts. Results: We demonstrate that by breaking the ecological barrier, massive introgressive hybridisation is possible between two endemic lineages of Cyprinidae belonging to two distinct genera. For both cohorts studied (=2 cm and >2 cm), a large majority of loci (>88%) presented no deviation in allele frequency and no departure from Hardy–Weinberg equilibrium. For individuals beyond the 2-cm stage, two phenomena were observed; the first was an allelic imbalance in favour of P. toxostoma, for some genomic regions, with genes involved in developmental regulatory processes, cytoskeletal organization, and chromosome organization. The second was an excess of heterozygous loci coupled with an equilibrium of allelic frequencies for genes involved in immune response and kidney/liver development. Moreover, the 2-cm-sized specimens with high mortality yielded a particular genomic signature. Conclusion: Our study displayed important results for understanding the early stages of hybridisation between divergent lineages and predicting the emergence of future hybrid zones in the wild. Moreover, this hybridisation generates a wide spectrum of hybrids that are a potential source of important evolutionary novelties.